Cardiorespiratory Fitness in Spanish Youth: The Roles of Sex, Age, Body Composition, and Healthy Lifestyle Habits in Cor-School Study - Saül Aixa-Requena; Álvaro Pano-Rodríguez; Vicenç Hernández-González; Enric Conesa-Milian; Abraham Batalla-Gavaldà; Jose Vicente Beltrán-Garrido; Isaac López-Laval; Francisco Corbi; Rosa Arnau-Salvador; Joaquín Reverter-Masia (Children)
Background/Objectives: Cardiorespiratory fitness (CRF) is a key indicator of current and future health in children and adolescents, and is influenced by both physiological and behavioral factors. This study examined the associations between CRF, body composition, and health-related habits in 685 children and adolescents (aged 8–16 years) who regularly participated in extracurricular sports programs in northeastern Spain. Methods: Participants underwent anthropometric assessments, completed a 20 m shuttle run test to evaluate CRF, and filled out validated questionnaires on physical activity levels, sleep quality, and adherence to the Mediterranean diet. Results: Significant sex differences were observed, with boys achieving higher CRF performance (p < 0.001), primarily associated with greater muscle mass (p < 0.001) and lower body fat percentage (p < 0.001). Age positively correlated with improved CRF (p < 0.001), whereas higher body mass index (p = 0.003) and fat mass (p = 0.020) negatively impacted fitness outcomes. Conclusions: These findings underscore the critical role of physical activity and optimal body composition in promoting cardiorespiratory fitness among youth, emphasizing the importance of targeted interventions to foster healthy behaviors from early childhood. Future research should adopt longitudinal designs to better elucidate the dynamic interactions between lifestyle factors, body composition, and physical fitness throughout childhood and adolescence.